Preventif Bullying dalam Perspektif Tafsir Al-Mishbah: Analisis Historis-Hermeneutis terhadap Kisah Yusuf - Fauziyyah, Wafa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
In the modern era, bullying, whether physical, verbal or cyber, has become a global crime issue that is widely reported in Indonesia. Assessing its relevance, this article analyzes the story of Prophet Yusuf AS in Surah Yusuf using J├╝rgen Habermas' historical-hermeneutical approach and Tafsir al-Mishbah. The aim is to find potential preventive values of bullying. The results show that the story of Yusuf contains significant preventive values. The interpretation of Tafsir al-Mishbah reveals that closeness, openness, and togetherness with parents are the keys to preventing bullying at an early stage. This finding confirms the historical-hermeneutical relevance of the story of the Prophet Joseph as a preventive foundation. The application of these values, especially the active role of parents, can be an effective strategy in shaping an environment that minimizes bullying in families and communities.